M/F Changes after T-loop Upper Horizontal Bending in Segmented Arch Mechanics - Muñoz-Rendón,Wilson A (Universidad de La Frontera. Facultad de Medicina, 2016)
bTi T-type loops are a frictionless, efficient alternative for extraction space closure. Changes in the upper horizontal portion of T-type loops to improve their mechanical behavior have been proposed, but differences in their biomechanical characteristics have not been well described. This stu dy analyzed the biomechanical differences among three T-type loops with differential bends in their upper horizontal portion. Ninety loops (0.017"x0.025" bTi) were bent and randomly divided in 3 groups according to the form of their upper horizontal portion (Tstraight, M convex, and C-loops concave), to evaluate force characteristics up to 6 mm of activation. Stiffness, maximum horizontal loads, total loop moments, and moment-to-force ratios were obtained. Nonparametric statistical analyses were used to test differences among groups. M-loops demonstrated lower force than T- and C-loops, and higher total loop moment than T-loops. A significant increase in M-loop moment-to-force ratio compared with T- or C-loops was obtained. C- and T-loops did not demonstrate significant differences in moment-to-force ratio between them. The convex upper bend in M-loops produced an increased total loop moment compared with T-loops. M-loops demonstrated moment-to-force values slightly higher than translation values, while the other loops reported only controlled inclination values at 6 mm of activation. M-loops are ideal when a higher control of root movement is indicated since the beginning of dental retraction in segmented arch mechanics.